Incorporating risk mitigation into building performance rating tools (BPRTs) for Malaysia’s Higher Education Building / Natasha Khalil - Natasha, Khalil (2016)
Higher educational buildings (HEB) are believed to have a key function that affects not only the environment, but also human and economic resources. Inevitably, the growing student population with various learning activities in public university buildings has exacerbated space inefficiency, ventilation discomfort and inadequacy of facilities. These malfunctions not only affect the buildings and sustainability, but in addition the users are also likely to be directly impacted in terms of health and safety risk. In accordance with the Government’s instruction on the holistic management of assets through General Circular (No.1) dated 27th March 2009, all managements should undertake a systematic approach to achieve building performance optimization. However, a proactive tool to measure performance and users’ risk is still lacking in the current assessment or maintenance of HEBs. Therefore, this research set out to develop a building performance risk rating tool, as a performance assessment measure concerning users’ health and safety risks in HEBs. The research has four objectives: i) to identify the current concept of building performance assessment used for HEBs, ii) to identify the indicators that contribute to the performance requirement and the users’ health and safety risk, iii) to determine the relative importance score as a weightage/rating in the construct of performance-risk indicators, and iv) to develop a building performance rating tool covering both building performance level and users’ risk level. This study adopted a mixed-mode approach that involves both quantitative and qualitative methods. To achieve the first and the second research objectives, the determinants of the indicators were initially compiled from the literature and the previous building assessment tool. They were further confirmed through semistructured interviews involving 18 building managers in Malaysia’s public HEBs. The findings identified 26 indicators to be incorporated into the list of assessments. They were categorised as functional, technical and indoor environmental performance indicators. In the next stage, questionnaires and the Analytical Hierarchy Process (AHP) method was used to achieve the third research objective. Twelve experts from the leading facilities management organisation agreed to participate in the survey rating process. The weightings of the indicators were extracted using the computer software, Expert Choice 11. The AHP results ranked five indicators as the most important indicators; structural stability (14.9%), fire prevention services (9.1%), building-related illnesses (7.4%), emergency exits (6.8%) and electrical services (6.3%). The total weightings from overall indicators also summed up the weights for technical performance (49.9%), functional performance (36.7%), and indoor environmental performance (13.4%). From this result, the proposed tool was developed based on the previous rating tool, and it comprised three steps of assessment. The first and the second steps evaluated each indicator, using the AHP weights and the performance assessment score. The third step summarised the assessed building by signifying a rating classification of “Excellent”, “Good”, “Medium”, “Low” or “Poor”, that suggests further action to improve performance and mitigate users’ health and safety risk. The proposed Building Performance-Risk Tool (BPRRT) has a significant contribution to make as an improved proactive measure for performance assessment in HEBs. The establishment of the BPRRT was successfully employed as an aid of improvement towards the current performance assessment of HEB by emerging the concept of building performance and risk into a numerical strategic approach. With this tool, explanatory studies of building performance and users’ risk can be conducted with more reliable data.